STUDENTS’ PERCEPTION ON THE USE OF VIDEO VLOG AS LEARNING MEDIA IN SPEAKING - Andewi, Widi (YHMM PUBLISHING, 2023)
Abstract Technological developments are currently widely used for the learning teaching process. It cannot be denied that speaking is the most crucial skill among three others skill in English. Improving speaking skills will help people to talk easily to each other and reduce misunderstandings in communicating with others. Learning through vlog media can be one of the most effective; this is very good where current students must be very familiar with technology. This study focused on students' perception of the learning process for their speaking skills using vlog as learning media. This research is qualitative descriptive research. The participants of the research were second-semester students of Institut Bakti Nusantara which consist of 10 students. Moreover, in achieving this research, the researcher used two types for data collections; that is interview and observation. The results of this research are vlog can make them more confident and improve their motivation to learn English, especially to speak English. Creating vlog increased students' self-confidence because it eliminated worry or fear of making mistakes when speaking English. The students felt free to talk because they didn't think anyone was watching and judging them. They are also motivated because this platform is familiar to them. Students also said that making a video vlog can improve their creativity.